2017
DOI: 10.1590/0102-311x00046516
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade infantil segundo cor ou raça com base no Censo Demográfico de 2010 e nos sistemas nacionais de informação em saúde no Brasil

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições, desde que o trabalho original seja corretamente citado.Caldas ADR et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
44

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 19 publications
0
16
0
44
Order By: Relevance
“…This evidence suggests they have not benefited equally from the country's dramatic improvements in infrastructure (housing, sanitation, and access to safe drinking water), health services, food security, nutrition, and elementary schooling over the last three decades. Disparities are also evident in indigenous children's health, including disproportionate morbidity and mortality due to preventable infections (Caldas et al, ; Cardoso et al, ; Escobar et al, ) and higher prevalence of undernutrition and anemia (Horta et al, ; Leite et al, ). Additionally, obesity and cardiovascular disease prevalence among adult indigenous women is catching up with the country's nonindigenous population due to recent accentuated nutrition transition (IBGE, ).…”
Section: Introductionmentioning
confidence: 99%
“…This evidence suggests they have not benefited equally from the country's dramatic improvements in infrastructure (housing, sanitation, and access to safe drinking water), health services, food security, nutrition, and elementary schooling over the last three decades. Disparities are also evident in indigenous children's health, including disproportionate morbidity and mortality due to preventable infections (Caldas et al, ; Cardoso et al, ; Escobar et al, ) and higher prevalence of undernutrition and anemia (Horta et al, ; Leite et al, ). Additionally, obesity and cardiovascular disease prevalence among adult indigenous women is catching up with the country's nonindigenous population due to recent accentuated nutrition transition (IBGE, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, studies on child mortality according to the ethnic-racial contour point to the complexity and challenges of expanding coverage of health services to different ethnic groups 5,7,8 . Thus, it is worth noting the improvement of the skin color/ethnicity variable in the live births and deaths certificates, reflected in the quality and coverage of the Health Information Systems, which allows greater reliability of health indicators for the planning of health actions and policies for the population 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Emphasizing the need for better knowledge of the mortality levels of Indigenous peoples in Brazil, some recent studies have given special attention to analysing data representative at a national scale, such as the information derived from the SIM and the 2010 Census [69,70]. For the 2009-2010 period, Caldas et al [69] reported significantly higher infant mortality rates for the Indigenous population (47.2 deaths per thousand live births according to the SIM data and 27.3 per thousand according to the 2010 Census) when compared to the figures for the Brazilian population overall (16.3 and 15.9 per thousand, respectively) [69].…”
Section: Ruralmentioning
confidence: 99%
“…Emphasizing the need for better knowledge of the mortality levels of Indigenous peoples in Brazil, some recent studies have given special attention to analysing data representative at a national scale, such as the information derived from the SIM and the 2010 Census [69,70]. For the 2009-2010 period, Caldas et al [69] reported significantly higher infant mortality rates for the Indigenous population (47.2 deaths per thousand live births according to the SIM data and 27.3 per thousand according to the 2010 Census) when compared to the figures for the Brazilian population overall (16.3 and 15.9 per thousand, respectively) [69]. Based on the data on deaths collected by the 2010 Census, Campos et al [70] investigated the probability of death in the Indigenous and non-Indigenous population according to gender in three age groups (0-4.9, 5 to 9.9 and 15 to 44.9 years), observing that the figures were always higher for men and for Indigenous people, sometimes as high as double among the first two age groups [70].…”
Section: Ruralmentioning
confidence: 99%